EMERGENCY TRAINING EFFECTIVENESS WITH CHAIR SIDE TALK METHOD ON MOTHER'S ABILITY IN TREATING CHILDREN'S FEVER SEIZURES - Karyo, Karyo; Ferianto, Kusno; Ayu Agustina, Ade (jfpublisher, 2022)
Introduction. Mothers are the most important role in the family when children are sick and mothers tend to be unprepared to deal with children with febrile seizures. Emergency training using the Chair Side Talk method is expected to provide mothers-to-be to increase their abilities if one day their child has a seizure. The purpose of this study was to determine the effectiveness of emergency training with the chair side talk method on the mother's ability to treat children's febrile seizures. Method. The research method used is pre-experimental , with a one group pre-post test design. The research sample was 28 women from Mander Village, Tambakboyo District who were selected by simple random sampling. SOP research instruments and questionnaire sheets. The analysis of this study used the Wilxocon test. Result & Analysis. The results showed that most of the mothers' abilities in dealing with children with febrile seizures before being given training were categorized as incapable, and after being given emergency training using the chair side talk method, most of them were categorized as capable. The results of statistical tests showed that there was a difference in the ability of mothers in handling febrile seizures after being given training with the chair side talk method with p value = 0.000 at a = 0.05 (p <0.05). It is hoped that after having the child's ability to have seizures, the mother can take care of the child during a seizure. Discussion. There is an effect of providing emergency training with the chair side talk method in handling febrile seizures.